2017
DOI: 10.1177/0733464816687218
|View full text |Cite
|
Sign up to set email alerts
|

Coping Resources, Loneliness, and Depressive Symptoms of Older Women With Chronic Illness

Abstract: Chronic illness with its accompanying physical stressors poses a risk factor for loneliness and depression in later life. Testing a model of stress and coping, we examined the effects of three types of coping resources (religious coping; Selection, Optimization, and Compensation [SOC] adaptive strategies; and perceived social support) on the deleterious effects of chronic illness among older women. Community-dwelling older women ( N = 138) with at least one chronic illness ( M = 3.9, SD = 2.1) completed mailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 80 publications
7
34
0
5
Order By: Relevance
“…Our results show that having more engagement in private religious activities is positive for well-being. Support for this finding was found in earlier studies among Christian populations in Western Europe (Braam et al, 2001) and in North America (Warner, Roberts, Jeanblanc, & Adams, 2017). We extended this finding by testing this in a population of predominantly Muslim Turkish and Moroccan immigrants.…”
Section: Discussionsupporting
confidence: 79%
“…Our results show that having more engagement in private religious activities is positive for well-being. Support for this finding was found in earlier studies among Christian populations in Western Europe (Braam et al, 2001) and in North America (Warner, Roberts, Jeanblanc, & Adams, 2017). We extended this finding by testing this in a population of predominantly Muslim Turkish and Moroccan immigrants.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, elderly individuals have been preparing for the battle with chronic disease, 4,14,23 and have been found to become depressed because of the symptoms of the illness, pain, disability, and loneliness during chronic illness. 24 Hence, research shows that depression among the elderly population is closely related to the presence of chronic diseases. 25 Other studies have indicated that the existence of chronic diseases, such as arthritis and kidney failure, is closely related to a high risk for suicidal thoughts and attempted suicide.…”
Section: Meaning Of Life Among Elderly Individuals 37mentioning
confidence: 99%
“…Esta disminución de masa muscular está directamente relacionada con la pérdida de fuerza, disminución de la capacidad funcional y empeoramiento de la calidad de vida relacionada con la salud (Goodpaster et al, 2006). Según diversos estudios (Amin et al, 2018;Warner, Roberts, Jeanblanc y Adams, 2017), el ejercicio físico tiene un efecto positivo sobre la salud física y mental debido a que produce liberación de endorfinas y esto, conlleva a una reducción de la ansiedad, la depresión y el estrés. Ya sea jercicio físico de bajo o alta intensidad, la liberación de estas sustancias actúan directamente sobre el cerebro, produciéndose una sensación de bienestar y relajación inmediata.…”
Section: Introductionunclassified
“…Además, inhiben las fibras nerviosas que transmiten el dolor, generando analgesia y sedación (Arruza et al, 2008). Todo ello produce un crecimiento de la autonomía personal y mayor autoestima en la población mayor que realiza ejercicio físico regular (Marshall, Schabrun, y Knox, 2017;Warner et al, 2017).…”
Section: Introductionunclassified